A mobile application as a supporting tool for weight equalisation in animal experiments. (26th February 2021) - Arogundade, Oluwasefunmi 'Tale; Akinola, Olufemi Sunday; Balogun, Motunrayo; Abayomi-Alli, Adebayo A.; Ikotun, Abiodun Motunrayo; Fadahunsi, Ibukun Grace; Abioye, Temitope Elizabeth
Weight equalisation (WE) is the technique of grouping experimental subjects with the aim of reducing the variability in the starting weight among experiment treatment groups. Existing methods are cumbersome, especially when dealing with large number of animals. This work developed a supporting tool for WE called WETool. It was implemented as an Android mobile application adopting quick sorting technique, Z score outlier detection with sinusoidal arrangement as the method for partitioning and sorting the experimental subjects into groups. Experimental data of 24 subjects were sorted using random sorting and WETool into six groups of four experimental subjects per group. Assigning the subjects resulted in group minimum weight that ranged from 13.75-10.125 and 12.5-12; with a difference of 3.625 and 0.5, per group; variance of 1.915 and 0.046 for random sorting and WETool respectively. The results of the acceptability evaluation of WETool were also very promising.